Pengaruh Konten Instagram @actforhumanity Terhadap Keputusan Berdonasi Pada Masa Pandemi Covid-19 : (Survei Pada Followers Akun Instagram @actforhumanity) - Ruth Endhita Malodo; Retno Dyah Kusumastuti (Prisani Cendekia Institute, 2022)
During the Covid-19 pandemic, invitations to donate, fundraising and social actions were widely echoed through social media. However, there are also many counterfeit online donation-raising activities which in the end make it increasingly difficult for people to put their trust in online donation-raising and it cannot be denied that it also affects people's decision to donate. In the midst of the rise of fake online donations, Aksi Cepat Tanggap (ACT) through its various online donation-raising content, nevertheless managed to attract sympathy and empathy from its donors. Therefore, this study aims to determine the magnitude of the influence of @actforhumanity's Instagram content on the decision to donate during the Covid-19 pandemic. This quantitative study uses Social Judgment Theory with the sampling technique of purposive sampling. The sample of this research is followers of the Instagram account @actforhumanity who have made donations to Aksi Cepat Tanggap (ACT) during the Covid-19 pandemic. In collecting data, this study used a questionnaire distributed to 100 respondents. In data analysis, the researcher used validity test, reliability test, simple linear regression test, coefficient of determination and hypothesis test using t test. It is easy to understand and the credibility of the content is the most influential indicator of the decision to donate during the Covid-19 pandemic. Based on the t-test, the t-count results were 10,917 > 1,660 t table. These results show that H0 is rejected and H1 is accepted. The results of the coefficient of determination test show that @actforhumanity's Instagram content has an influence of 54.9% on the decision to donate.